THE USE OF ABBREVIATIONS IN DIPLOMATIC TEXTS IN ENGLISH AND TAJIK LANGUAGES - SHARIPOV DURANDESH (JETA (Journal of English Teaching and Applied Linguistic), 2023)
This article is devoted to one of the key issues of linguistics, especially diplomatic and political abbreviations. In the process of research, we found that this abbreviation is not only used in the languages of other peoples, but it used in the Tajik language and has its own place in linguistics. In the course of the research, we found that most of the abbreviations are pronounced in capital letters. But some of them we can express through definition in the course of the study. However, abbreviations in the Tajik language also found their place and the corresponding modules.